Chondroblastoma arising in the temporal bone: A case report and literature review. Issue 4 (July 2020) - Tomioka, Takahiro; Yamada, Shin-ichi; Yoshimura, Nobuhiko; Gibo, Takahiko; Otagiri, Hiroki; Itoh, Ryuichi; Kakizawa, Yukinari; Suzuki, Hiroaki; Takumi, Yutaka; Yasunaga, Yoshichika; Kurita, Hiroshi
Abstract: Chondroblastoma is a rare bone tumor, accounting for less than 2% of all bone tumors. Tumors arising in the temporal bone are extremely rare. A 66-year-old female was referred to the ENT department with hearing disturbance on the right side. Computed tomography showed a mass with a bony defect on the right squamous part of the temporal bone and glenoid fossa. T2-weighted magnetic imaging revealed a low signal mass in the right squamous part of the temporal bone. The pathological diagnosis from a biopsy specimen was chondroblastoma. Complete resection of the tumor and reconstructive surgery were performed by the surgical team, which included ENT, brain, oral maxillofacial, and plastic surgeons. Histopathological findings of the surgical specimen revealed that mononuclear cells and multinucleated giant cells proliferated with extensive hemosiderin deposition with a background of fibrous tissue and a cartilage-like myxoid matrix. Immunohistochemically, the nucleus and cytoplasm of mononuclear cells were positive for the anti-S-100 protein antibody. Therefore, the pathological diagnosis of chondroblastoma was confirmed. The patient has been followed up for 5 years and 7 months postoperatively without any severe clinical disturbance or sign of recurrence.